EFFECTIVENESS OF VERMICOMPOST FERTILIZER DOSAGE AND PLANTING SPACING ON GROWTH AND YIELD OF BEANS (PHASEOLUS VULGARIS L.) - Muhammad Afrillah; Yuliatul Muslimah; All Rido Zamasi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The Indonesian people cultivate and consume a variety of legumes, including the beans (Phaseolus vulgaris L.). The demand for commodities on the market was rising every year, but there are still numerous challenges facing bean farmers today, including the issue of employing chemical fertilizers and applying them with the wrong spacing. Vermicompost fertilizer and correct spacing are two methods of improving bean growing technology that can be used to increase bean production. The aim of this study was to evaluate the effects of vermicompost fertilizer dosage and spacing on beans (Phaseolus vulgaris L.) growth and yield. The experimental garden at the University of Teuku Umar's Faculty of Agriculture served as the site for this study. This study's implementation started in January 2022 and ended in March 2022. Three replications of a 3 x 3 factorial randomized block design (RBD) were employed as the experimental design in this investigation. The amount of vermicompost fertilizer, which is composed of K1 (7.5 tons/ha), K2 (15 tons/ha), and K3 (22.5 tons/ha), as the first factor. The separation of J1 (50 cm x 30 cm), J2 (50 cm x 40 cm), and J3 (50 cm x 50 cm) as the second factor. Plant length, stem diameter, leaf area, and pod weight planted were all observed. The findings demonstrated a substantial impact of the optimal vermicompost fertilizer dose on the parameters of plant length at 14 and 21 day after plant (DAP) and the leaf area assessed in the K3 treatment (22.5 tons/ha). Additionally, none of the evaluated treatment were significantly impacted by the spacing factor.